Ответ(ы) на вопрос:
2)
x=6-3y
4(6-3y)-9y=3
24-12y-9y=3
-21y=3-24
-21y=-21
y=1
x=6-3*1=3
Ответ: (3; 1).
3)
x+(-x)+y+y=49+17
2y=66
y=66 : 2
y=33
x+33=49
x=49-33
x=16
Ответ: (16; 33).
2) [latex] \left \{ {4x - 9 = 3 } \atop {x + 3y = 6}} \right. [/latex]
[latex] \left \{ {{4(6 - 3y) - 9y = 3} \atop {x= 6 - 3y}} \right. [/latex]
[latex] \left \{ {-12y - 9y = -24 +3} \atop {x=6 - 3y}} \right. [/latex]
[latex] \left \{ {{-21y = -21 \ :(-21)} \atop {x= 6 - 3y}} \right. [/latex]
[latex] \left \{ {{y=1} \atop {x=6 - 3*1 = 3}} \right. [/latex]
3) [latex] \left \{ {{x + y = 49} \atop { -x + y = 17}} \right. [/latex] (+ и - ) между ними
[latex] \left \{ {{2y = 66 \:2} \atop { 2x = 32\:2}} \right. [/latex]
[latex] \left \{ {{y = 33} \atop { x = 16}} \right. [/latex]
Не нашли ответ?
Похожие вопросы